A matheuristic algorithm for the multi-depot inventory routing problem. (February 2019) - Bertazzi, Luca; Coelho, Leandro C.; De Maio, Annarita; Laganà, Demetrio
Highlights: We provide a mathematical formulation for the multi-depot Inventory Routing Problem. We design a three-phase matheuristic algorithm for solving the problem. We design and implement a branch-and-cut algorithm for solving the problem. We show the performance of the proposed matheuristic on a real case study. Abstract: In this paper we solve a practical Multi-Depot Inventory Routing Problem ( MDIRP ). One minimizes routing costs by determining how to serve the customers from different depots, managing their inventory levels to avoid stock-outs. The MDIRP optimizes the trade-off between inventory and routing decisions in an integrated way. We formulate this problem as a mixed-integer linear programming model and design a three-phase matheuristic to solve the problem. The solutions of our matheuristic are compared with those from a branch-and-cut algorithm on classical IRP instances, new instances and a real case study, showing to be very effective.